Consultation, Participation, and Disclosure of Information - The Inspection Panel (World Bank, Washington, DC, 2017)
This report on consultation, participation and disclosure of information is the fourth in a series of publications by the World Bank Inspection Panel drawing on the main emerging lessons from its caseload over nearly a quarter century. The Panel hope the lessons presented in this report can highlight areas in which continued improvements can enhance the Bank's and its member countries' overall approach to consultation, participation and disclosure of information as tools to empower affected person and communities to participate in development projects affecting their lives. The Inspection Panel was created in 1993 by the World Bank's Board of Executive Directors to receive and investigate complaints submitted by people suffering harm allegedly accused by Bank projects. As of September 2017, the Panel had received 120 requests for inspection. Of those, 90 had been registered and 34 investigated.